High-Performance Edge-Contact Monolayer Molybdenum Disulfide Transistors - Jiankun Xiao; Xiong Xiong; Xinhang Shi; Shiyuan Liu; Shenwu Zhu; Yue Zhang; Ru Huang; Yanqing Wu (Research)
Edge contact is essential for achieving the ultimate device pitch scaling of stacked nanosheet transistors with monolayer 2-dimensional (2D) channels. However, due to large edge-contact resistance between 2D channels and contact metal, there is currently a lack of high-performance edge-contact device technology for 2D material channels. Here, we report high-performance edge-contact monolayer molybdenum disulfide (MoS2) field-effect transistors (FETs) utilizing well-controlled plasma etching techniques. Plasma etching with pure argon improves the edge dangling bonds and thus improves the edge-contact quality. Edge-contact monolayer MoS2 FET shows good ohmic contact even at cryogenic temperatures (20 K), achieving a record-low contact resistance (Rc) of 1.25 kΩ·μm among all edge-contact MoS2 devices. The record-high on-state current of 436 μA/μm and transconductance of 123 μS/μm at Vds = 1 V are achieved on an edge-contact monolayer MoS2 FET with Lch = 120 nm. This work highlights the great potential of edge contacts for high-performance monolayer transition metal dichalcogenide (TMD) material electronics.